Guiné-Bissau: uma análise do sistema de gestão na escola pública - Uangna, Elia Maria Leandro (2023)
The present theme of the dissertation is entitled Guinea-Bissau: an Analysis of the Management System in the Public School and its scope is to discuss matters related to the Guinean educational system, in particular, the school management system, and to reflect on its past (pre-colonial, colonization and post-colonial periods) in order to understand the process of creating schools and their management. The Guinean educational system, in particular the public schools, over time, are faced with many difficulties in terms of functioning, with successive strikes, lack of infrastructure to house students, lack of minimum conditions for the proper functioning of classes and better use by students, not to mention teachers. The structure and the educational system itself are very centralized. This made adaptation to regional characteristics increasingly difficult, limiting community participation and insertion into the school environment. In these successive challenges, the fall of governments, changes in school management and the non- continuity of previous managers' projects demarcate determining elements of the process. It is believed that a stable and participatory management model can help to improve the functioning of the school. With this idea in mind, the following question is asked: what management concepts are evident in the guidelines of the Ministry of Education and in the way management is exercised in schools in Guinea-Bissau? What form of management could better contribute to qualifying educational work in schools? What is the role of the Regional Education Office in the management of schools? The general objective of the research is to analyze the functioning of the management of public schools in Guinea-Bissau and to identify the management concepts that are present in it. In a more targeted way, we aim to: analyze the school management system based on Ministry of Education documents; identify the policies implemented by the Ministry of Education in relation to the management of schools; understand how the management system of Basic Education schools (elementary and secondary) works from a public school in the city of Bissau; identify perspectives of school management and implications for its organization; to know, through observation at school and analysis of ME documents (Ministry of Education, Regional Education Office and school), the projects aimed at school management and proposals for education; verify the political-administrative and pedagogical organization of the schools, as well as the operation of their pedagogical administrative autonomy. To answer the questions raised above, we will analyze the documents that guide the management of Guinean schools (Basic Law of the Educational System and Inter Report of the observed school), the composition of the structure of the Ministry of Education, Regional Education Office and the structure of the school. Regarding the methodological issue, the research includes a qualitative approach in the field of educational policy, with a reflective analysis regarding the Guinean school management policy, through bibliographical and documentary research and, finally, field research, carried out by means of observation at school. As a conclusion, it is presumed that the Guinean education system still presents a model of unconsolidated school, due to the non-compliance with gratuity in unified basic education, inadequate infrastructure for the teaching and learning process of students, the non-consolidation of teaching language and non-compliance with the school year calendar. On the other hand, the management of Guinean education needs and must be rethought from the Ministry of Education to get to the bottom of the schools and their separation in relation to party politics.